Current Nonoperative Therapeutic Interventions for Lower Gastrointestinal Hemorrhage - Serur, Anna; Rhee, Rebecca; Ramjist, Joshua (Clinics in Colon and Rectal Surgery, 2020)
Lower gastrointestinal hemorrhage remains a common cause of hospitalization, with significant health care costs. Initial management should include aggressive resuscitation followed by localization of bleeding with nuclear scintigraphy, colonoscopy, or computed tomography (CT) angiography. If bleeding does not resolve spontaneously, expeditious intervention with minimally invasive endoscopic or angiographic methods is necessary with surgical intervention as a last resort.
Keywords: lower gastrointestinal bleed; angiography; colonoscopy; CT angiography